Peran Content Creator Media Sosial dalam Perspektif Sosiologi Komunikasi di Era Endemi Covid-19 - Muna Khansa Mufidah (IAIN Salatiga, 2023)
The use of social media has now become a necessity and even a priority for some Indonesian people, including the millennial generation. Moreover, since the Covid-19 outbreak in 2020, so many workers have switched professions to become content creators. On the other hand, we have seen a lot of various news in the mass media, ranging from the report of success obtained by using social media to information about kidnapping, fraud, prostitution, and so on. But from another point of view, the sociology of communication will provide an explanation that is relevant to the current situation of society, so that every individual, including content creators as members of society, can adapt to the development of various phenomena that arise in their society. The purpose of this study was to determine the role of social media content creators from the perspective of the sociology of communication in the Covid-19 endemic era. The research method uses a qualitative approach to phenomenology. Data collection techniques using observation, interviews, and documentation. Provisions on the number of informants selected based on purposive sampling technique, as many as 7 youths. The research findings were analyzed by qualitative descriptive analysis. The results showed that seven content creators created content with themes related to real life, such as culinary, da'wah, tahsin science, home design, typography, Canva design, and copywriting. From the perspective of the sociology of communication, content creators have a significant role in providing content that is informative, educative, inspiring, entertaining, and profitable for the audience.